Like Mother, Like Daughter: Intergenerational Programs for Hispanic Girls - Maria Luisa Gonzalez; Joanna Glickler; Cynthia Risner-Schiller (Educational Considerations, 1995)
Hispanic mothers' involvement with and expectations of their children coupled with their position as role-models, have a lasting impact on their children's academic achievement.